Early metformin treatment improves pancreatic function and prevents metabolic dysfunction in early overfeeding male rats at adulthood. Issue 12 (3rd November 2020) - Previate, Carina; Malta, Ananda; Miranda, Rosiane Aparecida; Martins, Isabela Peixoto; Pavanello, Audrei; de Oliveira, Júlio Cezar; Prates, Kelly Valério; Alves, Vander Silva; Francisco, Flávio Andrade; Moreira, Veridiana Mota; Matiusso, Camila Cristina Ianoni; de Moraes, Ana Maria Praxedes; et al.
Abstract : New Findings: What is the central question of this study ? Studies reported the efficacy of metformin as a promising drug for preventing or treating of metabolic diseases. Nutrient stresses during neonatal life increase long‐term risk for cardiometabolic diseases. Can early metformin treatment prevent the malprogramming effects of early overfeeding? What is the main finding and its importance? Neonatal metformin treatment prevented early overfeeding‐induced metabolic dysfunction in adult rats. Inhibition of early hyperinsulinaemia and adult hyperphagia might be associated with decreased metabolic disease risk in these animals. Therefore, interventions during infant development offer a key area for future research to identify potential strategies to prevent the long‐term metabolic diseases. We suggest that metformin is a potential tool for intervention. Abstract: Given the need for studies investigating the possible long‐term effects of metformin use at crucial stages of development, and taking into account the concept of metabolic programming, the present work aimed to evaluate whether early metformin treatment might program rats to resist the development of adult metabolic dysfunctions caused by overnutrition during the neonatal suckling phase. Wistar rats raised in small litters (SLs, three pups per dam) and normal litters (NLs, nine pups per dam) were used as models of early overfeeding and normal feeding, respectively. During the first 12 days of suckling, animals from SL and NL groups received metformin, whereas the controls received saline injections. Food intake and body weight were monitored from weaning until 90 days of age, when biometric and biochemical parameters were assessed. The metformin treatment decreased insulin concentrations in pups from SL groups, and as adults, these animals showed improvements in glucose tolerance, insulin sensitivity, body weight gain, white fat pad stores and food intake. Low‐glucose insulinotrophic effects were observed in pancreatic islets from both NL and SL groups. These results indicate that early postnatal treatment with metformin inhibits early overfeeding‐induced metabolic dysfunctions in adult rats. Abstract :